ENHANCING STUDENTS’ SPEAKING ACHIEVEMENT THROUGH TIME TOKEN TECHNIQUE - Silvia, Resi (LPPM Universitasdiwangsa Jambi, 2020)
The main focus of the study was to know whether Time Token Technique effective or not to enhance English speaking achievement of second year nursing students of University of Adiwangsa Jambi. The study was mix research in which combination of quantitative and qualitative approaches were used in this research. 33 nursing students of second year were selected be samples through total sampling procedure. The data was collected through pre-test and post-test, video shooting, and field note. The main findings of the study were: the value of t-test is bigger than t-table and there is raising students’ speaking achievement percentage that involves pronunciation, grammar, fluency and vocabulary from pre-test to post-test. Moreover, this technique can help inactive student to be more active to speak English every day, increase self-confident, vocabulary and improve pronunciation and grammar.